Novel therapies for metastatic castrate-resistant prostate cancer - Dayyani, Farshid; Gallick, Gary E; Logothetis, Christopher J; Corn, Paul G (JNCI : Journal of the National Cancer Institute, 2011)
Recent advances in tumor biology have made remarkable achievements in the development of therapy for metastatic castrate-resistant prostate cancer. These advances reflect a growing appreciation for the role of the tumor microenvironment in promoting prostate cancer progression. Prostate cancer is no longer viewed predominantly as a disease of abnormally proliferating epithelial cells but rather as a disease of complex interactions between prostate cancer epithelial cells (epithelial compartment) and the surrounding tissues (stromal compartment) in which they reside. For example, prostate cancers frequently metastasize to bone, an organ that contains a microenvironment rich in extracellular matrix proteins and stromal cells including hematopoietic cells, osteoblasts, osteoclasts fibroblasts, endothelial cells, adipocytes, immune cells, and mesenchymal stem cells. Multiple signaling pathways provide crosstalk between the epithelial and the stromal compartments to enhance tumor growth, including androgen receptor signaling, tyrosine kinase receptor signaling, and immune surveillance. The rationale to disrupt this "two-compartment" crosstalk has led to the development of drugs that target tumor stromal elements in addition to the cancer epithelial cell.